PENINGKATAN PRESTASI BELAJAR MATEMATIKA MATERI PERKALIAN MELALUI MEDIA ABAKUS BAGI SISWA TUNANETRA - Herwanto, Sugeng (program Studi Pendidikan Luar Biasa FKIP Universitas Sebelas Maret, 2013)
The aim of this research is improving mathematic ?calculate multiplication? learning acvhievements using abacus for the fourth grade of elementary students with visual impairment of SLB Negeri I Pemalang 2012/2013 academic year. The approach of the research is classroom action research conducted by planning, implementation, observation and reflection. The subject of this study were the three students of the fourth grade of elementary students with visual impairment of SLB Negeri I Pemalang 2012/2013. Data validity used in the study is content validity and the data analysis technique used was comparative descriptive analysis by comparing test scores between two cycles, the test scores of students before and after using abacus. Based on research that has been conducted, it can be concluded that mathematic learning using abacus improved the mathemathic ?calculate multiplication? learning achivements for the fourth grade of visual impaired elementary students of SLB Negeri I pemalang simester I, 2012/2013 academic year within the students? learning achivement for 57 in cycle I and 77 in cycle II. Keywords: Abacus, visual impairment, learning achievement